Graphenes as additives in photoelectrocatalysis. Issue 32 (26th July 2017) - García, Alejandra; Fernandez-Blanco, Cristina; Herance, Jose R.; Albero, Josep; García, Hermenegildo
Abstract : Due to the electrical conductivity, charge mobility and large surface area, graphenes in small weight percentages can increase the efficiency of semiconductors in photoelectrodes. The review covers CO2 generation, H2 evolution and pollutants degradation. Abstract : Due to their electrical conductivity, graphenes in small weight percentages can increase the efficiency of semiconducting catalysts. Besides conductivity, other reasons for this beneficial influence of graphenes on PEC are the large contact area with the particles of the semiconductor and the fast electron migration from the conduction band of the semiconductor to graphenes, enhancing charge separation efficiency and lifetime. The purpose of the present review is to show how addition of graphenes increases the photoelectrocatalytic activity of semiconductors as photoanodes or photocathodes. The existing literature has been grouped according to the photoelectrocatalytic reaction, including CO2 reduction, H2 generation and pollutant degradation, putting emphasis on the photoelectrode preparation, since it determines the properties of the resulting composite. The final section summarizes the state of the art and forecasts future developments in the field.